Study of Sustainable Development Goals (SDGS) Quality Education in Indonesia in the First Three Years - Novianita Rulandari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The aim of this study is to conduct research and analysis on Indonesia's progress toward the Sustainable Development Goals (SDGs) Quality Education over the last three years (2015-2018). The aim of this study is to assess and comprehend Indonesia's progress toward achieving the Sustainable Development Goals (SDGs) for Quality Education since they were announced in 2015. In Indonesia, the Sustainable Development Goals (SDGs) and Education Quality thesis utilizes a qualitative research design. We conducted this research using a case study analysis based on the procedure, the data, and the triangulation of sources. We draw certain conclusions as a result of the study. To begin, in comparison to four years ago, at the time of the SDGs' initial ratification, Indonesia experienced better progress in terms of timeliness and participatory processes. But even so, the challenges faced by implementing the SDGs are not just about those two things. In terms of substance, the ambition of SDGs to eliminate the negation component of the development is a work that is almost close to utopia. Second, in terms of the process, the implementation of SDGs Quality Education at the national level still leaves homework such as accountability mechanisms, receipt of data from non-government parties, and the participation process itself. This should not be seen as a burden but rather a challenge that must be faced to improve performance for the acceleration of Indonesia's quality education national development until 2030. Third, the active role of the government is certainly the main capital for the implementation and achievement of SDGs quality education in Indonesia. Initiatives that come from various parties, including universities, bring optimism that the SDGs quality education will be implemented on inclusive and participatory principles. Fourth, a coalition of civil society organizations is needed to ensure that the SDGs' quality education is implemented in the context of Indonesia's growth, both at the national and regional levels. These social systems have the potential to pressure the Indonesian government to prepare for a variety of things, both procedurally and substantively.